METHODS OF TREATING CANCER - HATTERSLEY Gary; GARNER Fiona (2025)
Disclosed herein are methods of inhibiting tumor growth or producing tumor regression in a subject having a drug-resistant estrogen receptor alpha positive cancer or a mutant estrogen receptor alpha positive cancer. The methods entail administering to the subject a therapeutically effective amount of RAD 1901 having the structure (I) or a salt or solvate thereof. En este documento se describen métodos para inhibir el crecimiento tumoral o producir regresión tumoral en un sujeto que tiene un cáncer positivo a receptor de estrógeno alfa resistente a fármaco o un cáncer receptor positivo de receptor de estrógeno alfa. Los métodos implican administrar al sujeto una cantidad terapéuticamente eficaz de RAD1901 que tiene la estructura: (ver Fórmula) o una sal o solvato del mismo.